Mechanical System Dynamics - Pfeiffer, Friedrich (Lecture Notes in Applied and Computational Mechanics,, 2008)
This textbook gives a clear and thorough presentation of the fundamental principles of mechanical systems and their dynamics. It provides both the theory and applications of mechanical systems in an intermediate theoretical level, ranging from the basic concepts of mechanics, constraint and multibody systems over dynamics of hydraulic systems and power transmission systems to machine dynamics and robotics. The book aims at practicing engineers, researchers and graduate students in mechanical engineering and mechanics. The concept of the book is mainly determined by the experiences of the author. Sixteen years aerospace industry with its forerunner role in all technologies, but also in many fundamentals, twenty years academia in the area of mechanics, especially in the areas of dynamics and control, fundamental research on bilaterally and unilaterally constrained systems, on robotics and walking machines and many applications with regard to practical industrial problems. Both theory and practice were topics of more than eighty dissertations being carried through during his activities as Professor and head of an Institute at the Technical University of Munich.